Avaliação das dimensões transversais e análise da resistência à fratura de mini-implantes ortodônticos fabricados no Brasil - Gadêlha, Flávio Paiva (2007)
This work aims at to clarify referring points to the mechanics resistance of these devices and its relation with some transversal measures of the auto-armor-piercing mini-implants of some diameters of three national manufacturers: Conexão, Neodent and Sin. A sample of 36 mini-implants divided for diameter in 6 groups had been evaluated. The evaluated diameters had been 1,3 mm, 1.4 mm, 1.5 mm, 1.6 mm and 1.8 mm. The mini-implants had been measured in its diameters in three points in the height of its neck: D1- neck or trans-gingival portion; D2- nucleus of the thread soon after the neck; D3- external portion of the first thread step soon after the neck. The results were compared to the diameter supplied for the manufacturer. Later, all the mini-implants had been tested the breaking resistance through torsion assay, getting as resulted the Torque of Rupture (TR) and the Angular Deflection of Rupture (ADR). The results showed that only the Neodent mini-implants 1,3 and 1,6 mm had presented measures coincident with the values supplied for the manufacturer. The mini-implants had presented a TR and a ADR medium in each group of, 20 N.cm and 174,23 ° for the Neodent 1,3 mm; 33,9 N.cm and 85° for the Sin 1,4 mm; 26,4 N.cm and 57,47 ° for the Conexão 1,5 mm; 37,5 N.cm and 187,73 ° for the Neodent 1,6 mm ; 48,2 N.cm and 151 ° for the Sin 1,6 mm; e 67,8 N.cm and 143,67 ° for the Sin 1,8 mm. Spearman and Pearson tests showed positive correlation between the TR for the mini-implants of Neodent and Sin, but the correlation was weak. The statistical evaluation between the DAR and the diameters measured accused a low correlation for all manufacturers and diameters studied. It follows that factors such as, design of the mini-implants, and others can be related to the resistance to fracture the mini-implants.